Ozone Activates the Nrf2 Pathway and Improves Preservation of Explanted Adipose Tissue In Vitro - Barbara Cisterna; Manuela Costanzo; Alice Nodari; Mirco Galiè; Serena Zanzoni; Paolo Bernardi; Viviana Covi; Gabriele Tabaracci; Manuela Malatesta (Antioxidants, 2020)
In clinical practice, administration of low ozone (O3) dosages is a complementary therapy for many diseases, due to the capability of O3 to elicit an antioxidant response through the Nuclear Factor Erythroid 2-Related Factor 2 (Nrf2)-dependent pathway. Nrf2 is also involved in the adipogenic differentiation of mesenchymal stem cells, and low O3 concentrations have been shown to stimulate lipid accumulation in human adipose-derived adult stem cells in vitro. Thus, O3 treatment is a promising procedure to improve the survival of explanted adipose tissue, whose reabsorption after fat grafting is a major problem in regenerative medicine. In this context, we carried out a pilot study to explore the potential of mild O3 treatment in preserving explanted murine adipose tissue in vitro. Scanning and transmission electron microscopy, Western blot, real-time polymerase chain reaction and nuclear magnetic resonance spectroscopy were used. Exposure to low O3 concentrations down in the degradation of the explanted adipose tissue and induced a concomitant increase in the protein abundance of Nrf2 and in the expression of its target gene Hmox1. These findings provide a promising background for further studies aimed at the clinical application of O3 as an adjuvant treatment to improve fat engraftment.